Etične dileme pri rehabilitaciji onkoloških bolnikov - Kuret, Zala (Rehabilitacija (Ljubljana), 2017)
With the progress of medicine and the aging of the population in the recent years, we are faced with the growing number of cancer patients, who have a variety of problems. These can be managed with rehabilitation procedures, during which we encounter many ethical dilemmas. In the rehabilitation of cancer patients we follow the basic ethical principles of harmlessness, beneficence, respect for patient's autonomy and fairness. The principle of beneficence requires the identification of the patient's problems that are manageable with known and accessible rehabilitation procedures, while considering and respecting the patient's wishes. According to the fairness principle, all the patients (regardless of nationality, gender, education, cultural or social background) participate in the procedures that are useful for them. Depending on the individual patient, we must choose an appropriate program and rehabilitative environment, which will be tailored to the stage of disease and patient's capabilities and needs. In this paper, we address ethical dilemmas in the terminal stages of the disease, dilemmas in conjunction with pain management, nutrition, and also the problem of burnout of healthcare workers who treat cancer patients.
Keywords: bolečina; cancer; ethical issues; Ethics; etične dileme; food; Neoplasms; nutrition; oncology; onkologija; pain; prehrana; rak; rehabilitacija; rehabilitation; terminal illness; terminalna bolezen; vocational rehabilitation